057 GOSH-wide review of pancreatitis as a complication in methylmalonic aciduria. (December 2018) - Forny, P; Davison, J; Skeath, R; Gruenewald, S; Stojanovic, J; Hadzic, N; Barone, G; Vara, R; Munir, S
Abstract : Background: Methylmalonic aciduria (MMA) is an autosomal recessive disorder of propionate metabolism characterized by the accumulation of methylmalonic acid and other metabolites in tissues and body fluids. The disease often manifests with an acute decompensation early on in life, presenting with lethargy, vomiting, hypotonia, metabolic acidosis and hyperammonaemia. Patients who survive the initial presentation are at risk of long-term complications, including acute and chronic basal ganglia injury, white matter disease and optic neuropathy, as well as tubulointerstitial nephritis, leading to progressive renal failure. Pancreatitis is another reported severe complication, but only limited data are available with regards to epidemiology, diagnostics and best management of this complication. This study aimed to review the epidemiology of pancreatitis in a large single-centre cohort of patients with MMA. Methods: Retrospective review of 37 MMA patients' records (n=22 classical MMA and n=15 vitamin B12-responsive MMA) identified 10 (27%) who had at least one episode of pancreatitis adjudged by the Atlanta Criteria (2/3 of: clinical symptoms, elevated amylase or lipase (>3 times upper limit of normal), radiological signs). 7 had recurrent or chronic pancreatitis. Pancreatitis was more prevalent in those with vitamin B12 non-responsive MMA, and in those with neonatal onset MMA. Review of 22 distinct episodes of pancreatitis showed that lipase was more sensitive than amylase in detecting pancreatitis. 4/10 had ultrasound imaging abnormalities of pancreas at first episode. 3 had significant chronic imaging abnormalities. Results: This review emphasises the importance of pancreatitis in MMA. The higher incidence reported here may reflect previous under-recognition. All acutely ill MMA patients should be assessed for pancreatitis, particularly when symptoms including abdominal pain or vomiting are present. Further research is required to determine the aetiology, optimum medical and nutritional management strategies and potential preventative measures.